IMPACT OF EARLY MARRIAGE ON MARITAL RELATIONSHIPS AMONG WOMEN OF A PERI URBAN VILLAGE OF NORTH INDIA - Chintu Chaudhary; Ruchi Pandey; Sameena Ahmad; Mohd Najmul Aqib Khan; Vishal Bankwar; Rambha Pathak; Shubham Girdhar (The Indonesian Journal of Public Health, 2022)
Introduction: Early marriage has long been a problem in developing countries as it not only affects the health of girls but also deprives them of a childhood that they rightfully deserve. Apart from this, marital relationship in case of early marriage is also not as fruitful as compared to late marriages owing to emotional immaturity of the females. Methods: This study was conducted to estimate the prevalence of early marriage and its association with marital relationship. It was a community based cross-sectional study conducted among 322 married females in field practice areas of JNU-IMRC, Jaipur, Rajasthan. Result: The study found that 53.4% of the females had married before the age of 18 years. Significant association of marital age was observed with education status, socioeconomic status, nature of employment and education status of the male partner (p<0.05). Also, choosing friends and expressing opinions to elders, as a part of autonomy and self-efficacy, respectively, were found to be associated with early marriage (p>0.05). Conclusion:The study established that early marriages are still prevalent in the country. Ongoing efforts through the existing programs in the country need to reach the right audience especially in the rural areas.